ANALISIS KEUNGGULAN KOMPARATIF DAN KOMPETITIF USAHA PENGOLAHAN SAGU DI KABUPATEN KONAWE - Sarty Syarbiah; Ayub M. Padangaran; Darwis Darwis; Budiyanto Budiyanto (Jurnal Sosio Agribisnis, 2017)
The purposes of this research were to analyse the level of comparative and competitive advantage of sago processing enterprises in Konawe Regency; to analyse the impact of government policy on the comparative and competitive superiority of sago processing enterprises in Konawe regency. This study was conducted from March to June 2013 on 30 samples as the source of data. The data were collected from interview, and the method of sago processing was analyzed with Policy Analysis Matrix (PAM). The results of the study shown that the level of comparative and competitive superiority of sago processing enterprises in Konawe regency was at DRCR = 0,38 and PCR = 0,45. The local government policy concerning inputs in comparative and competitive superiority of sago processing enterprises shown a decrease of EPC = 0,77, and the policy regarding the price for sago processing outputs was Rp. -1.188.000, which suggested that the government policy has not been in favor of the sago processing enterprises. Keywords: sago, processing enterprises, comparative, competitive, advantages